Rare Case of Iliopsoas Abscess Secondary to Mucinous Adenocarcinoma of the Colon: A Case Report - Menon, Aditya (J Orthop Case Rep, 2018)
INTRODUCTION: Iliopsoas abscess (IPA) has varied clinical symptomatology and various clinical disorders may mimic it. Tuberculosis of spine is the most common source of secondary IPA in the developing countries. However, IPA may be rarely caused by colon cancer which is the most common gastrointestinal malignancy. A mixed culture gives an indication of gastrointestinal or genitourinary etiology. We present here, a rare case of an 86-year-old patient with IPA secondary to adenocarcinoma of colon. CASE REPORT: An 86-year-old female presented with pain in the right thigh in February 2014. Computed tomography (CT) scan and magnetic resonance imaging (MRI) of the abdomen confirmed the clinical suspicion of right IPA which was drained surgically. Intraoperatively, mucinous material was noted, emerging from a small opening in a rounded structure located lateral to the psoas muscle, which could not be identified. On post-operative day 2, the right flank swelling recurred. Culture reports showed a polymicrobial infection with viridans group Streptococci and Pseudomonas aeruginosa. The abscess was re-explored and biopsy of the opening was taken. Histopathology of the tissue sample revealed metastatic cells of a mucin-secreting adenocarcinoma that had infiltrated the psoas muscle with a secondary pyogenic abscess. On reviewing the CT scan, there was a suspicion that the abscess was communicating with a tumor in the colon. No further active intervention was done for the tumor in view of advanced age and stage of tumor. The patient had significant pain relief and was able to resume walking. The infection resolved with 6 weeks of oral linezolid and ciprofloxacin. The patient died 8 months later secondary to metastasis. CONCLUSION: Although the diagnosis of IPA does not pose problems, diagnosing secondary IPA requires a high index of clinical suspicion. A Gram-negative culture must raise the suspicion of gastrointestinal or genitourinary pathology. Colon carcinoma, although extremely rare, can lead to secondary IPA. CT and MRI though extremely useful, may not pick up the pathology and a definitive diagnosis of colon neoplasia perforating into the psoas muscle may be evident only intraoperatively. Atypical presentation may delay the diagnosis of colon cancer and subsequently result in higher morbidity and mortality.